THE USING OF LEARNING MODELS IN THE BIOLOGY LEARNING PROCESS ON UNDERSTANDING CONCEPTS AND STUDENTS’ MOTIVATION IN INVERTEBRATE CONCEPT - Fajriana, Nurul (Jurnal Biologi Sains dan Kependidikan, 2022)
This study aims to determine the use of learning models on understanding concepts and students' motivation in invertebrate concept in class X at SMA Negeri 1 Sukamakmur. The research method used in this study is a survey method. The subjects in this study were biology teachers who teach in class X and students in class X at SMA Negeri 1 Sukamakmur. The instruments used in this study were questionnaires and interviews. Questionnaires were used to obtain data on student responses about student learning motivation in invertebrate concept. Interviews were conducted to obtain information about the using of learning models in invertebrate concepts used by teachers. The data collection technique was carried out by distributing questionnaires to class XI students to find out student responses regarding student learning motivation in invertebrate concept. Then interviews were conducted with the teacher to get answers from the teacher by means of one-sided questions and answers regarding the learning model used by the teacher in studying invertebrate concept. The data obtained were then analyzed descriptively. Based on the results of data analysis, it is known that the learning model used by the teacher when teaching invertebrate concept is Jigsaw. However, the learning model has not been able to improve students' conceptual understanding, this can be seen from the average score obtained by students which is still far below the minimum completeness criteria (KKM) that has been set by the teacher, namely with an average value of only 31. Meanwhile, the results of the analysis The questionnaire shows that 53% of students are motivated to learn and 47% of students are not motivated to learn about invertebrate concept. Almost half of the total number of students are not motivated in learning From the results of the study it can be concluded that not all learning models are suitable for use in every concept. This can be seen from the scores obtained by students who have not yet reached the KKM and the learning model used by the teacher has not been able to increase students' motivation in studying invertebrate concept.